Aligning ERP systems with companies' real needs: an 'Operational Model Based' method. Issue 2 (7th February 2017) - Mamoghli, Sarra; Goepp, Virginie; Botta-Genoulaz, Valérie
Abstract : Enterprise Resource Planning (ERP) systems offer standard functionalities that have to be configured and customised by a specific company depending on its own requirements. A consistent alignment is therefore an essential success factor of ERP projects. To manage this alignment, an 'Operational Model Based' method is proposed. It is based on the design and the matching of models, and conforms to the modelling views and constructs of the ISO 19439 and 19440 enterprise-modelling standards. It is characterised by: (1) a predefined design and matching order of the models; (2) the formalisation, in terms of modelling constructs, of alignment and misalignment situations; and (3) their association with a set of decisions in order to mitigate the misalignment risk. Thus, a comprehensive understanding of the alignment management during ERP projects is given. Unlike existing methods, this one includes decisions related to the organisational changes an ERP system can induce, as well as criteria on which the best decision can be based. In this way, it provides effective support and guidance to companies implementing ERP systems, as the alignment process is detailed and structured. The method is applied on the ERP project of a Small and Medium Enterprise, showing that it can be used even in contexts where the ERP project expertise level is low.